Investment, Islamic Human Development Index and Banking Financing on Economic Growth and Their Impact on Labor Absorption - Daulay, Ahmad Harun; Asmuni, Asmuni; Harahap, Isnaini (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
The purpose of the study was to analyze the effect of investment, the Islamic Human Development Index and banking financing on the economic growth of the districts/cities of North Sumatra province and to analyze the effect of economic growth in mediating the effect of investment, the Islamic Human Development Index and banking financing for employment in the districts/cities of North Sumatra province. The use of the path analysis method with economic growth as the intervening variable results that in total the indirect effect of investment, banking financing and the Islamic Human Development Index through the intervening variable of economic growth on the Open Unemployment Rate is significant, which means that Economic Growth is able to mediate the effect of Investment, Banking Financing and Islamic Human Development Index on the Open Unemployment Rate in Regencies/Cities of North Sumatra Province during 2015-2019. The amount of direct influence between all variables used, namely, Economic Growth to the Open Unemployment Rate is 90 percent, where the magnitude of the direct influence between all the variables used, namely; Investment, Banking Financing and Islamic Human Development Index on Economic Growth is 95.96 percent. Economic growth as an intervening variable is able to mediate the effect of Investment, Banking Financing and the Islamic Human Development Index (IHDI) on the Open Unemployment Rate and Wage Workers, Banking and Islamic Human Development Index on Workers' Wages, Banking and Islamic Human Development Index on Workers' Wages. The influence of economic growth on the open unemployment rate is positive and significant and the influence of economic growth on workers' wages is negative and significant. The direct influence of economic growth on workers' wages is 89.87 percent.